Pengaruh Beban Kerja, Kepuasan Upah, dan Keadilan Organisasi terhadap Turnover Intention Karyawan dengan Kepuasan Kerja sebagai Variabel Moderasi: Studi Kasus PT. Bank Muamalat KC Medan Balikota - Dea Dara Audina; Maryam Batubara; Nurul Jannah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of the study (Case Study of Bank Muamalat KC Medan Balaikota) is to determine the effect of organizational honesty, satisfaction with salary and satisfaction of work on the employee’s turnover intent by using satisfaction by work as a moderator variable. The study was conducted on 35 employees, both as a population and as a sample. This study uses simple samples. The method of analysis is double regression. Double linear regression analysis is used in this study. The software used is SPSS 22. Thro the study, it has been demonstrated that wage satisfaction has a negative and significant impact on the workload and fairness within the organization, while wage satisfying has a positive and substantial impact on employee intentions for turnover and labor burden both negative and substancial. Keywords: workload, salary satisfaction, fairness of organization, job satisfaction, turnover intention.